Utilization of the Taspen Authentication Application for Pension Customer Services at PT. Bank Mandiri Taspen Baturaja Branch Office (KCP) - Dani Atmaja; Khoirudin , Khoirudin; Ona Saputri (LP2M IAIN Palopo, 2025)
This study examines the effectiveness of the Taspen Authentication application in improving pension customer satisfaction at PT Bank Mandiri Taspen Baturaja Branch Office (KCP). This application is designed to facilitate the digital pension fund payment process through facial and voice authentication, which is expected to accelerate service and reduce the need for physical customer presence. Descriptive qualitative methods were used to obtain data through in-depth interviews, observations, and documentation studies with key participants, namely employees and pension customers. The results show that the application generally simplifies access and accelerates the fund disbursement process, increasing efficiency and user satisfaction. However, the application's effectiveness is still hampered by technical constraints such as the sensitivity of the biometric system and network disruptions during peak transaction times, as well as external factors such as low technological literacy, physical limitations, and language barriers among elderly users. The study recommends the development of a more adaptive biometric system, increased network capacity, intensive training for users, and the provision of manual services as an alternative for customers who are unable to use digital applications. These findings strengthen the literature on digital technology adaptation in the pension services sector and serve as an important reference for the development of an adaptive and sustainable inclusive digital service strategy at PT Bank Mandiri Taspen.